Protective Role of R-spondin1, an Intestinal Stem Cell Growth Factor, against Radiation-Induced Gastrointestinal Syndrome in Mice - Bhanja, Payel (Public Library of Science, 2009)
BACKGROUND: Radiation-induced gastrointestinal syndrome (RIGS) results from a combination of direct cytocidal effects on intestinal crypt and endothelial cells and subsequent loss of the mucosal barrier, resulting in electrolyte imbalance, diarrhea, weight loss, infection and mortality. Because R-spondin1 (Rspo1) acts as a mitogenic factor for intestinal stem cells, we hypothesized that systemic administration of Rspo1 would amplify the intestinal crypt cells and accelerate the regeneration of the irradiated intestine, thereby, ameliorating RIGS. METHODS AND FINDINGS: Male C57Bl/6 mice received recombinant adenovirus expressing human R-spondin1 (AdRspo1) or E.coli Lacz (AdLacz), 1–3 days before whole body irradiation (WBI) or abdominal irradiation (AIR). Post-irradiation survival was assessed by Kaplan Meier analysis. RIGS was assessed by histological examination of intestine after hematoxilin and eosin staining, immunohistochemical staining of BrdU incorporation, Lgr5 and β-catenin expression and TUNEL staining. The xylose absorption test (XAT) was performed to evaluate the functional integrity of the intestinal mucosal barrier. In order to examine the effect of R-spondin1 on tumor growth, AdRspo1 and AdLacZ was administered in the animals having palpable tumor and then exposed to AIR. There was a significant increase in survival in AdRspo1 cohorts compared to AdLacZ (p<0.003) controls, following WBI (10.4 Gy). Significant delay in tumor growth was observed after AIR in both cohorts AdRspo1 and AdLacZ but AdRspo1 treated animals showed improved survival compared to AdLacZ. Histological analysis and XAT demonstrated significant structural and functional regeneration of the intestine in irradiated animals following AdRspo1 treatment. Immunohistochemical analysis demonstrated an increase in Lgr5+ve crypt cells and the translocation of β-catenin from the cytosol to nucleus and upregulation of β-catenin target genes in AdRspo1-treated mice, as compared to AdLacz-treated mice. CONCLUSION: Rspo1 promoted radioprotection against RIGS and improved survival of mice exposed to WBI. The mechanism was likely related to induction of the Wnt-β-catenin pathway and promotion of intestinal stem cell regeneration. Rspo1 has protective effect only on normal intestinal tissue but not in tumors after AIR and thereby may increase the therapeutic ratio of chemoradiation therapy in patients undergoing abdominal irradiation for GI malignancies.